1996
DOI: 10.1021/la950902r
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneities in Sheared Ultrathin Lubricating Films

Abstract: Nonequilibrium molecular dynamics computer simulations have been used to study nanoscopically confined oligomer films under shear. Beyond the well-known density layering across such films, other structural and dynamical inhomogeneities exist across such films and are discussed here. When these films are subjected to strong shear flows, slip appears at the confining surfaces or inside the pore, depending on the wall interactions. For strong wall affinities interlayer slip develops between the adsorbed layer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 47 publications
(120 reference statements)
7
65
0
Order By: Relevance
“…As the reorientation of the nanofiller takes places, the viscosities of such nanodispersions approach the initial viscosity of the pure polymer with rising shear-rate (Mittal, 2012). This phenomenon has been reported by several other studies for synthetic polymers (Giannelis, 1996;Manias et al, 1996;Krishnamoorti et al, 2001) and for biopolymers (Tunc et al, 2007;Echeverría et al, 2014). Similar results were obtained when the WPI content of nanocomposite dispersions rose to 15% (w/w) (Figure 2).…”
Section: Viscosity Measurementsupporting
confidence: 85%
“…As the reorientation of the nanofiller takes places, the viscosities of such nanodispersions approach the initial viscosity of the pure polymer with rising shear-rate (Mittal, 2012). This phenomenon has been reported by several other studies for synthetic polymers (Giannelis, 1996;Manias et al, 1996;Krishnamoorti et al, 2001) and for biopolymers (Tunc et al, 2007;Echeverría et al, 2014). Similar results were obtained when the WPI content of nanocomposite dispersions rose to 15% (w/w) (Figure 2).…”
Section: Viscosity Measurementsupporting
confidence: 85%
“…Water was released high as 20%. This suggests that PEO, when adsorbed from the RCMs in two steps with increasing temperaon the silicate surface, replaces water in agreement with ture as shown by two representative examples (Mol, previous observations.3,6,7, 12 Low contents of PEO and Mo5). The amount of relatively weakly bound water water in the Mo7 and Mo8 samples could be explained (released below 100 'C) was higher in Mo5 (about 16.5% by the presence of collapsed interlayers, in which less compared to 12% in Mol).…”
supporting
confidence: 81%
“…The force fields used in this simulation study 1996, 8, 1597-1599. are based on a geometrically fitted and optimized combination of force fields used in previous studies of apparent in both dry and hydrated systems. These hydrated montmorillonite'°- 12 and PEO-salt sysfeatures include the preferred locations of ions and the tems.13" 4 Silicate atoms have been completely condisordered bilayer structure of the polymer. strained in all cases.…”
mentioning
confidence: 99%
“…As for layering, the rate of decay is determined by g(r). It has been studied extensively for spherical molecules [17,18,22,23,25,26], but only recently for chain molecules [35,46,47]. In part, this is because most studies of chain molecules near surfaces have neglected the discrete lattice structure of the solid surface.…”
Section: Equilibrium Structurementioning
confidence: 99%
“…As the film thickness decreases, confinement can induce a phase transition to a crystalline or glassy phase [25,28,29,30,31,32,33,34]. Near the glass transition, films exhibit a non-Newtonian response with the same power law viscosity seen in experiments [9,10,29,30,31,32,35]. Studies of crystalline films of spherical molecules showed that stick-slip motion resulted from periodic phase transitions between sliding fluid and static solid phases [28,31].…”
Section: Introductionmentioning
confidence: 99%